First record of Hypostomus roseopunctatus (Siluriformes: Loricariidae) for Argentina - Teran, Guillermo Enrique (2020)
In this note we expand the known distributional range of Hypostomus roseopunctatus to the political boundaries of Argentina. The sole specimen was obtained in the Miriñay River, Uruguay River basin, province of Corrientes. With this record the number of Hypostomus species known from Argentina raises to 26.